Antibacterial Acitivity of Esssential Oils of Selected Medicinal Plants on the Causative Agents of Respiratory Infections in Pediatric Population - Bogdanović, Svetlana; Zlatković, Ivana; Veličković, Ana; Ranđelović, Dobrila; Zlatanović, Zvonko (Medical Word, 2024)
Acute respiratory infections (ARI) are the most common infectious diseases today and are the reason for as many as 75% of prescribed antibiotics in the world. For this reason, ARI is responsible for the emergence of bacterial resistance to the most commonly used antibiotics. The paper aimed to examine the potential antibacterial activities of the essential oil of medicinal plants Lavandula angustifolia Mill., Mentha spicata L., Chamomilla recutita (L.) Raushert, Salvia officinalis L., Urtica dioica L., from the region of southeastern Serbia, on bacteria associated with respiratory infections in the pediatric population. Relevant, dichotomous keys were used to determine the plant material. The extraction of the essential oil was performed with a Clevenger-type apparatus, while the antibacterial activity was examined with an aromatogram, using the disk-diffusion method. Statistical analysis was performed with a one-factor ANOVA test. The use of essential oils can be an alternative solution to combat multidrug-resistant bacteria. In our research, the oil of Salvia officinalis L. showed the strongest inhibitory effect against Moraxella sp., while the oil of Chamomilla Recutita (L.) Raushert showed the weakest effect against Haemophilus sp. In general, the essential oil of Chamomilla recutita (L.) Raushert showed the weakest effect against all isolated pathogens. The essential oil of the investigated plants can be used as a potential source of natural antibacterial compounds. Because of all the above, it is necessary to further investigate and identify the biologically active compounds of the investigated plants.